A mean weight analysis of Classic Nabatean lamp sherds from Roman Aila (Aqaba, Jordan). (16th June 2021) - Lapp, Eric C.
Abstract: A mean weight analysis was conducted on Classic Nabatean type lamp sherds (N = 75) unearthed at the Red Sea port of Roman Aila (Aqaba, Jordan). The purpose of this essay is to independently test and replicate Diedre Barrett's mean weight methodology to verify its viability as a procedure to determine the estimated original complete lamp count for this group at the site. The study further suggests modifications to the analysis and proposes an equation to express the mean weight procedure.